2019
DOI: 10.1017/langcog.2019.38
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological signatures of English onomatopoeia

Abstract: Onomatopoeia is widespread across the world’s languages. They represent a relatively simple iconic mapping: the phonological/phonetic properties of the word evokes acoustic related features of referents. Here, we explore the EEG correlates of processing onomatopoeia in English. Participants were presented with a written cue-word (e.g., leash) and then with a spoken target-word. The target-word was either an onomatopoeia (e.g., bark), a sound-related but arbitrary word (e.g., melody), or another arbitrary word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In an ERP investigation of iconicity, Lockwood and Tuomainen (2015) found a more positive P2 associated with iconic stimuli, which is often associated with phonological processing and multisensory integration. In addition, Vigliocco, Zhang, Del Maschio, Todd, and Tuomainen (2020) hypothesized that an N400 effect should emerge between onomatopoeic and non-onomatopoeic words if there is a direct link between phonology and semantics for iconicity, and indeed this is what they found.…”
Section: The Role Of Phonology In Iconicity Effectsmentioning
confidence: 80%
See 1 more Smart Citation
“…In an ERP investigation of iconicity, Lockwood and Tuomainen (2015) found a more positive P2 associated with iconic stimuli, which is often associated with phonological processing and multisensory integration. In addition, Vigliocco, Zhang, Del Maschio, Todd, and Tuomainen (2020) hypothesized that an N400 effect should emerge between onomatopoeic and non-onomatopoeic words if there is a direct link between phonology and semantics for iconicity, and indeed this is what they found.…”
Section: The Role Of Phonology In Iconicity Effectsmentioning
confidence: 80%
“…As behavioural effects of iconicity in language processing tasks have been mixed, with some studies showing an effect (Meteyard et al, 2015;Sidhu et al, 2020) and others not (Peeters, 2016;Vigliocco et al, 2020), it seems fair to assume that iconicity effects in lexical processing tasks are subtle, and vulnerable to factors such as list context, task context, and individual differences among participants.…”
Section: The Role Of Phonology In Iconicity Effects 35mentioning
confidence: 99%
“…Similarly, reduced N400 responses for words with iconic mapping between forms and meanings relative to arbitrary words were observed in an event-related potentials (ERPs) study, which suggests a processing advantage for highly iconic words (Peeters, 2016). Larger N400 effects have also been reported for onomatopoeias preceded by arbitrary words in a semantic relatedness task, suggesting enhanced semantic processing of onomatopoeias, which in turn allows for improved detection of the mismatch between primes and targets (Vigliocco, Zhang, del Maschio, Todd, & Tuomainen, 2020). In another study, Lockwood and Tuomainen (2015) observed facilitated processing of iconic adverbs compared to arbitrary adverbs as indexed by enhanced P2 and late positive component effects.…”
Section: Introductionmentioning
confidence: 83%
“…Many such associations are found in the vocabularies of thousands of natural languages (Blasi, Wichmann, Hammerstrom, Stadler, & Christiansen, 2016). Importantly, iconicity facilitates not just word learning (for reviews, see Imai andKita, 2014, andNielsen andDingemanse, 2021) but also, according to a couple of studies, word meaning access (Peeters, 2016;Vigliocco, Zhang, Del Maschio, Todd, & Tuomainen, 2020). This suggests that iconicity might supplement a lack of distributional information.…”
Section: Phonesthemes and Iconicitymentioning
confidence: 99%